Dynamics on the Pre-periodic Components of the Fatou Set of Three Transcendental Entire Functions and Their Compositions - Subedi, Bishnu Hari; Singh, Ajaya (Nepal Journal of Science and Technology, 2020)
We prove that there exist three transcendental entire functions that can have an infinite number of domains which lie in the pre-periodic component of the Fatou set each of these functions and their compositions.